2014
DOI: 10.4103/1658-354x.144059
|View full text |Cite
|
Sign up to set email alerts
|

Between pain and pleasure: Pregnant women′s knowledge and preferences for pain relief in labor, a pilot study from Zaria, Northern Nigeria

Abstract: Background:Pain relief in labor remains a hot topic and these debates get louder by the day as more women become aware of their rights to better quality of care in labor. This study was conceived in a background where the practice of pain relief in labor is evolving and where women are seeking to fulfill their need for pain-free labor.Objective:To investigate the knowledge, utilization and preferences of methods of pain relief in labor by expectant mothers in order to design a labor analgesia program.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Similar results indicating the major source of information being from their friends and relatives were found in earlier studies too [15,16]. In contrary, a study done in Northern Nigeria showed the majority of women have heard of pain relief mostly from their caregivers and during the current pregnancy [12]. The level of awareness was also high in the said study which could be attributed to increasing discussions on the topic during antenatal visits.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results indicating the major source of information being from their friends and relatives were found in earlier studies too [15,16]. In contrary, a study done in Northern Nigeria showed the majority of women have heard of pain relief mostly from their caregivers and during the current pregnancy [12]. The level of awareness was also high in the said study which could be attributed to increasing discussions on the topic during antenatal visits.…”
Section: Discussionsupporting
confidence: 82%
“…Such low levels of utilization may be partly due to lack of knowledge, however it was found that even a very high number of women still were ready to bear the pain in their upcoming labor. It is prevalent in low resource settings too [11,12]. However it was also noted that the desire to bear the labor pain was much lower in women with previous experience which indicates that labor is a big source of pain and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study done in Nigeria showed that women were worried about side effects on their babies (20%) or on themselves (17%), whereas some concerns were related to extra fees (3%) [14]. In our study, although 91% of HPs agreed to give pain relief during labor if facilities were available, 80.8% of them had some concerns regarding its use.…”
Section: Discussionmentioning
confidence: 56%
“…Studies conducted in Nigeria have demonstrated differences in the level of pain reported by parturients from different tribal groups and between “westernized” and non‐westernized individuals [12]. Other work conducted in Nigeria found that many parturients were unaware of their rights regarding pain relief, frequently did not receive pain relief despite requesting it, and were fearful of caregivers and perceived side effects [16]. However, Nigerian patients have been demonstrated to have a high uptake of analgesia when it is offered [17].…”
Section: Discussionmentioning
confidence: 99%